DOMINANT FACTORS AFFECTING SEDIMENT OXYGEN CONSUMPTION LEVEL IN INTENSIVE WHITE SHRIMP (Litopenaeus vannamei) POND - Hidayat S. Suwoyo; K. Nirmala; D. Djokosetiyanto; Sri R.H. Mulyaningrum (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2015)
Sediment oxygen consumption level is an indicator of mineralization procces intensity and indicator of microorganism activity in the substrate, and also a description of dissolved oxygen consumption or utilization in a water body. This study aimed to evaluate factors of sediment quality which influenced sediment oxygen consumption level. The study was conducted at the experimental pond installation of Research Institute for Coastal Aquaculture (RICA), in Punaga, Takalar Regency, South Sulawesi, using two units of 4000m2 intensive ponds with density of 50ind./m2. Rearing period was approxi-mately in 4months. Pond management was carried out in accordance with standard operating pro-cedures. Homogeneity between experimental units was approached by the uniformity of pond management including pond preparation, shrimp seed management, feed management,and water management. Sediment quality variables measured were redox potential, pH, total organic matter, sediment oxygen consumption, total bacteria, and production aspect. The results showed that the factors which have close relationship with the sediment oxygen consumption were redox potential, organic matter, and total bacteria. The model could be used to predict the sediment oxygen con-sumption on white shrimp pond with the following regression equation Y= 0.0000496 + 0.00025 organic matter + 0.00037 total bacteria - 0.00000948 potential redox with R2 = 0.847.Keywords: sediment oxygen consumption, sediment quality, pond, Litopenaeus vannamei